The Role of Culture On Service Failure Perceptions and Service Recovery Expectations In Restaurants - Mustafa ÜLKER (Akdeniz University Tourism Faculty, 2021)
In this study, the aim is to examine the service failures encountered in restaurants and the recovery efforts that consumers expect in response to service failures in the context of cultural values. A qualitative research approach was adopted, and data were collected from nine tourist guides through semi-structured interviews. Content analysis was used for data analysis. The results show that service failures are categorized as (a) failures in the kitchen, (b) failures in the presentation of services, and (c) general failures while service recoveries are categorized as (i) compensatory responses, (ii) empathetic responses, and (iii) corrective responses. As the results indicate, Turkish tourists care more about failures in the kitchen. Contrary to this, American tourists care more about failures in the presentation of services. Furthermore, Turkish tourists expect compensatory and corrective responses in kitchen-based failures, on the other hand, American tourists expect compensatory responses.